Analisis Semen Babi Yorkshire dalam Modifikasi Extender Alami Buah Lontar dalam Filtrat Jambu Air Hijau (Syzygiumaqueum) - Foeh, Nancy; Datta, Frans Umbu; Gaina, Chyntia D. (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2024)
This study aims to see the effectiveness of Yorkshire boar semen natural modification of the natural diluent of green guava filtrate (Syzygiumaqueum). Semen is stored per 72 hours from a 3-year-old sow. Macro and microscopic evaluation of semen includes Volume, Colour, Consistency, pH, Odor and motility, concentration, viability, abnormality and normality of spermatozoa. The semen was diluted with palm fruit juice and added green guava filtrate (Syzygiumaqueum) in tiers: 100μL, 200μL, 300μL, 400 μL and 500 μL. The results showed that the modification of palm fruit juice diluent with the addition of 200 μL of green guava filtrate (Syzygiumaqueum) in Yorkshire boar semen was able to maintain the quality of spermatozoa up to 22 hours of storage.